Media representation of children's privacy in the context of the use of "smart" toys and commercial data collection - Milosevic, Tijana (Array, 2019)
The growing use of “smart” toys has made it increasingly important to understand the various privacy implications of their use by children and families. The article is a case study of how the risks to young children’s privacy, posed by the commercial data collection of producers of “smart” toys, were represented in the media. Relying on a content analysis of media coverage in twelve European countries and Australia collected during the Christmas season of 2016/2017, and reporting on a follow-up study in selected countries during the Christmas season of 2017/2018, our article illustrates how the issue of children’s privacy risks was dealt with in a superficial manner, leaving relevant stakeholders without substantive information about the issue; and with minimum representation of children’s voices in the coverage itself.